Standard Modifiable Cardiovascular Risk Factors Mediate the Association Between Elevated Hair Cortisol Concentrations and Coronary Artery Disease - Stomby, Andreas; Strömberg, Susanna; Theodorsson, Elvar; Olsen Faresjö, Åshild; Jones, Mike; Faresjö, Tomas (Frontiers in Cardiovascular Medicine, 2022)
Background Increased cortisol exposure is a risk factor for coronary artery disease (CAD). It is not clear to what degree this risk is independent from the standard modifiable risk factors (SMuRFs) dyslipidemia, hypertension and diabetes. Aim To use path analysis to test the direct and indirect association, mediated by SMuRFs, between long-term cortisol levels measured in hair (HCC) and CAD. Method Hair was sampled from patients admitted with acute myocardial infarction (n = 203) and a population-based sample without a diagnosis or symptoms of CAD (n = 3134). The HCC was analyzed using radioimmunoassay and all participants reported whether they were diagnosed with or treated for diabetes, hypertension, and hyperlipidemia. Path analysis was used to test to what degree the association between logarithmized (ln) HCC and CAD was direct or indirect, mediated by SMuRFs. Results Participants with CAD had elevated HCC compared to those without (median (IQR): 75.2 (167.1) pg/mg vs. 23.6 (35.0) pg/mg, P < 0.0001). Higher HCC was associated with diabetes, hypertension, and hyperlipidaemia which in turn were associated with CAD. In path models, 80% of the association between ln(HCC) and CAD was mediated by SMuRFs, while the direct path between ln(HCC) and CAD was not statistically significant. Conclusion The SMuRFs diabetes, hyperlipidaemia and hypertension mediate the association between ln(HCC) and CAD. Some association between ln(HCC) and CAD did not operate via the SMuRFs considered, and might have a pathway through atherosclerosis or inflammation.